Fluorescence Quenching of Graphene Quantum Dots by Chloride Ions: A Potential Optical Biosensor for Cystic Fibrosis - Ifrah, Zahid; Shah Rukh, Abbas; Muhammad Nauman, Sharif; Maryam, Shahid; Rahat, Ullah (Frontiers in Materials, 2022)
Cystic fibrosis is a genetic disorder caused by a mutation in the CFTR gene that codes ABC transporter-class ion channel protein resulting in sticky and thick mucous secretion which clogs the airwa4ys and leads to respiratory failure and other complications. It also results in higher Clˉ ions in body fluids. Cystic Fibrosis is generally detected using sweat chloride test and ion exchange chromatography which are lab restricted. Therefore, there is a dire need to develop portable assays to monitor circulatory changes (Clˉ ion detection) to detect CF at the point of care. In this work, fluorescence quenching of graphene quantum dots (GQDs) was used as a property of optical sensor for chloride ions detection. GQDs were synthesized by varying carbonizing temperature and time, then their optical and fluorescence (FL) quenching was investigated upon exposure to chloride ions in comparison with different ionic species. GQDs synthesized at 160°C (50 minutes) were chosen as they displayed the highest fluorescence. The physicochemical and optical characterization confirmed the preparation of 12-15nm GQDs, which were amorphous in nature with the peak emission observed at 362nm, at an excitation wavelength of 370nm. The fluorescence quenching response of GQD with the Clˉ ions displayed linearity up to 100mM with a correlation coefficient of 0.98, and the lowest detection limit of approximately 3mM Clˉ ions.